PENERAPAN MEDIA INTERAKTIF BERBASIS GAME ULAR TANGGA UNTUK MENINGKATKAN KONSENTRASI BELAJAR SISWA SDN KARANGDEMPEL 01 - Usuludin Amali; Didik Tri Setiyoko; Rila Melyana Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of applying an interactive media based on the snakes and ladders game to improve learning concentration in Grade V at SDN Karangdempel 01. The background of the research stems from low student concentration to the continued use of conventional teaching methods that do not actively engage students. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 25 students in class VA (experimental group) and 25 students in class VB (control group). Data collection instruments included written tests, observation sheets, and student response questionnaires. The results showed that the implementation of interactive media using the snakes and ladders game significantly improved students’ concentration compared to conventional learning methods. The study concludes that educational games such as snakes and ladders can serve as effective, engaging, and enjoyable learning tools to enhance the quality of teaching and learning processes in elementary schools.